World Allergy Organization Journal - Fiocchi, Alessandro; Jensen-Jarolim, Erika
World Allergy Organization Journal publishes original research, clinical reviews, position papers, and epidemiological studies that contribute to current knowledge in patient care. With authors, reviewers and readers representing all geographic regions, the journal provides a truly global perspective on allergy, asthma and clinical immunology. WAO Journal aims to publish works with specific clinical relevance and practical measures that are critical for the practice of allergy anywhere in the world, which examine issues of drug and aspirin sensitivity, drug desensitization, natural history of allergic diseases, asthma, atopic dermatitis, and environmental and socio-economic concerns that impact the practice and delivery of care for allergic diseases and that have so far not received the attention they deserve. The journal provides a vehicle to highlight newer approaches for the evaluation of disease and outcomes concerning treatments and interventions, and keep abreast with evolving developments in informatics, telemedicine, and web-based learning. The journal also emphasizes basic and clinical translational science in allergy and immunology to address pathogenic mechanisms in allergic diseases and examine new, cutting-edge information that extends our understanding of pathogenesis and disease function. Technical advances (including evaluation of systems biology, nanotechnology, and other new approaches to the science of allergy and immunology) and the application of new paradigms and technologies influencing our understanding of the pathogenesis of allergic disease are preferred. With the intent to capture and discuss the latest advances, the journal seeks manuscripts on the new roles of cytokines, innate immune system reactions, tissue remodeling, immunopharmacology, pharmacogenomics, and so forth.